Pengaturan Kepemilikan Hak Atas Tanah bagi Yayasan Penyelenggara Pendidikan - Idris, Vidiya Indriani; Santoso, Budi (JURNAL USM LAW REVIEW, 2023)
The phenomenon of HM foundation’s land rights ownership occur amongst peoples in society as the result of administrative ignorance which has received less attention from the majority of foundations as a legal entities. This can cause various problems if the Foundation does not immediately conveying the rights of the land. This study aims to find legal certainty in obtaining land rights for the Educational Organizing Foundation (YAU) and the implementation of land grants belonging to foundations on behalf of individuals when the parties whose names are attached to the certificate is die and the heirs concerned are abroad. This study use qualitative research methods based on empirical juridical research types. The results of the study show that the acquisition of land rights for YAU as a legal entity that cannot have HM land rights over its land, the arrangement for obtaining the land rights will apply like an ordinary legal entity which can only have land rights in the form of HGB, HGU, and usage rights. The transfer of YAU's land rights was carried out based on PP No. 40 of 1996. The implementation of land grants belonging to foundations on behalf of individuals is carried out on a legal and strong basis for foundations to obtain juridical rights to their land through a statement letter from the heirs. The transition through land grants was chosen to implementing arrangements for the acquisition of foundation assets that have been regulated in UUY. Banyak ditemuinya status kepemillikan HM atas tanah yayasan di masyarakat menjadi persoalan ketidak tertiban administrasi yang kurang diperhatikan oleh berbagai yayasan sebagai badan hukum. Hal ini dapat menimbulkan berbagai problema bila yayasan tidak segera membalik nama tanah tersebut. Penelitian ini bertujuan untuk menemukan kepastian hukum dalam perolehan hak atas tanah Yayasan Penyelenggara Pendidikan (YAU) dan pelaksanaan hibah tanah milik yayasan yang diatasnamakan perorangan ketika pihak yang namanya melekat dalam sertifikat meninggal dunia serta ahli waris yang bersangkutan berada di luar negeri. Penelitian ini menggunakan metode penelitian kualitatif yang didasarkan pada jenis penelitian yuridis empiris. Hasil penelitian menunjukkan bahwa perolehan hak atas tanah bagi YAU sebagai badan hukum yang tidak dapat memiliki status HM atas tanahnya maka pengaturan perolehan hak atas tanahnya akan berlaku seperti badan hukum biasa yang hanya dapat memiliki hak atas tanah berupa HGB, HGU, dan Hak Pakai. Peralihan hak atas tanah YAU dilakukan berdasarkan PP No. 40 Tahun 1996. Pelaksanaan hibah tanah milik yayasan yang diatasnamakan perorangan ini dilakukan dengan dasar yang sah dan kuat bagi yayasan untuk memperoleh hak yuridis atas tanahnya melalui surat pernyataan dari para ahli waris. Peralihan melalui hibah tanah dipilih untuk tetap mengimplementasikan pengaturan perolehan aset kekayaan yayasan yang telah diatur dalam UUY.